Benzotriazole as Privileged Scaffold: A Molecular Docking Approach toward Breast Cancer Drug Discovery - Tambe, Pornima Ramdas; Bhor, Rohit Jaysing; Kolhe, Mahesh Hari; Varade, Radhika Bansi; Bhaiya, Shaikh Tarnnum; Tambe, Akanksha Sunil (Asian Journal of Biological and Life Sciences, 2026)
Introduction: Breast cancer remains one of the leading causes of cancer-related mortality worldwide, particularly in hormone receptor–positive subtypes driven by estrogen signaling. In the present study, a structure-based molecular docking approach was employed to evaluate benzotriazole derivatives as potential aromatase inhibitors. Materials and Methods: The crystal structure of human aromatase (PDB ID: 3EQM) was retrieved from the Protein Data Bank and prepared using standard protein optimization protocols. Results: Twelve benzotriazole derivatives (PT-1 to PT-12) were designed and subjected to ligand preparation, energy minimization, and docking analysis using the Schrodinger Glide module. All compounds complied with Lipinski’s criteria, while PT-5 exhibited one Veber violation due to high polarity. Docking scores ranged from −6.22 to −9.90 kcal/mol, indicating favorable binding interactions with the aromatase active site. Discussion: Notably, PT-5 demonstrated the strongest binding affinity (−9.90 kcal/mol), forming multiple conventional hydrogen bonds with VAL369, VAL370, PRO429, MET311, and THR310, along with hydrophobic and π–interactions. PT-4 and PT-11 exhibited balanced docking performance and favorable pharmacokinetic profiles, suggesting improved drug-likeness compared to PT-5. Interaction analysis revealed that residues VAL369, VAL370, ALA306, ALA307, LEU152, PHE430, MET303, and CYS437 play crucial roles in ligand stabilization through hydrogen bonding, π–π stacking, π–sulfur, and hydrophobic interactions. Conclusion: The conclusion was the findings highlight benzotriazole as a promising scaffold for aromatase inhibition and support further in vitro and in vivo investigations to validate its therapeutic potential in breast cancer management.
Keywords: Benzotriazole; Molecular Docking; Anticancer Activity; Aromatase Inhibitor; PDB-3EQM